Energy utilization, nutrient digestibility and bone quality of broiler chickens fed Tanzania-type diets in different forms with enzymes - Chang’a, Edwin Peter (J Anim Sci Technol, 2019)
A study was conducted to determine the influence of feed form and microbial enzyme supplementation on energy utilization, bone quality, and amino acid and mineral digestibility of broiler chickens. Four hundred and eighty Ross 308, day-old broiler chickens were randomly assigned to eight diets formulated from commonly used ingredients in Tanzania. A 2 (pellet or mash) × 4 (control, Axtra XB, Quantum Blue (QB) and Axtra XB + QB enzyme) factorial array in a completely randomized design having six replicates per treatment (10 birds per replicate) was used. Birds were raised in climate-controlled rooms in a 3-phase; starter (0–10 days), grower (11–24 days) and finisher (25–35 days). Apparent metabolizable energy (AME), metabolizable energy intake, net energy of production, energy retained as protein (REp), and efficiency of metabolizable energy use for energy and protein retention were higher (p < 0.05) in birds fed pelleted diets. The AME and REp was higher (p < 0.05) with enzyme supplementation. Ash content, weight, length, width and breaking strength of tibia bones were highest (p < 0.05) in birds on pelleted diets. Tibia bone traits were improved (p < 0.05) when enzymes were included, particularly in a combination of QB and Axtra XB. However, potassium, magnesium, and zinc contents were highest (p < 0.05) when QB was supplemented. Digestibility of all amino acids was higher (p < 0.05) in birds supplied with pellets and with enzyme supplementation for most amino acids, except for serine. There was a positive interaction (p < 0.05) between feed form and enzymes on lysine and phenylalanine digestibility. Digestibility of Ca, P, K, S, Zn, and Fe was higher (p < 0.05) in birds fed pelleted diets, while those on mashed diets had higher (p < 0.05) digestibility of Cu and B. The digestibility of P, K, and Zn was highest (p < 0.001) when QB was added, while Ca, P, S, and B digestibility was highest when a combination of Axtra XB + QB was applied. Pelleted diets with or without enzymes improved energy utilization, digestibility of amino acids, and minerals, and increased bone strength in broiler chickens.